Comparison of hook-wire and medical glue for CT-guided preoperative localization of pulmonary nodules - Zhang, Huijun; Li, Ying; Chen, Xiaofeng; He, Zelai (Frontiers in Oncology, 2022)
Background: Preoperative localization is challenging due to the small diameter of pulmonary nodules or their deep location in the lung parenchyma during VATS surgery. The purpose of this study was to compare the efficacy and safety of both hook-wire and medical glue for pre-operative localization of pulmonary nodules. Methods:158 patients were retrospectively analyzed (January 2019 and January 2020). The patients underwent hook-wire or medical glue for pre-operative localization of pulmonary nodules. Among them, 74 patients in the hook-wire group and 84 patients in the medical glue group underwent VATS anatomic segmentectomy or wedge resection after localization of pulmonary nodules. All records of patients with pre-operative localization were collated, and the efficacy and safety of the two methods were evaluated according to localization success rates and localization-related complications. Results: The success rate of localization in the medical glue group was 100 % and 97.3 % in the hook-wire group. After localization of the pulmonary nodules, the incidence of minor pneumothorax in the medical glue group (11.9%) was lower than that in the hook-wire group (37.8%) (p=0.01). The incidence of mild pulmonary parenchymal hemorrhage in the medical glue group (13.1%) was also lower than that in the hook-wire group (24.3%) (p=0.000). The mean time from the completion of localization to the start of surgery was also longer in the medical glue group than in the hook-wire group (p=0.000). The mean visual analog scale (VAS) after localization was higher in the hook-wire group than in the medical glue group (p=0.02). In both groups, parenchymal hemorrhage was significantly associated with the needle length in hook-wire localization and the depth of the medical glue in the lung parenchyma (p = 0.009 and 0.001, respectively). Conclusion: These two localization methods have been shown to be safe and effective in pre-operative pulmonary nodule localization. The medical glue localization method had fewer complications, a higher success rate, less pain in localization, and more flexibility in the arrangement of operation time.